Effect of White Turmeric Extract (Curcuma zedoaria) Using Zam-zam Solvent Compare with Ethanol Solvent Against Breast Cancer Cell T47D - Hudaya, Isna; Nasihun, Taufiqurrahman; Sumarawati, Titiek (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2015)
Introduction: Curcuma zedoaria is one of the herbal plants potentially protects and cures many diseases, particularly as anti-cancer and anti-tumor. Anti-cancer active compounds of it are flavonoid, phenolic, and saponin. Objectives: This study aimed to explore the cytotoxicity of Curcuma zedoria extract (CZE). Methods: Experimental Quasi with post test non equivalent control group design on T47D cell line at Biology laboratory, Faculty of Medicine, Sultan Agung Islamic University, Semarang. The research was consisted of 2 groups, namely: intervention group with CZE zam-zam solvent and intervention group with CZE ethanol solvent given 10 different dosages each for 1.000 Î¼g/mL; 500 Î¼g/mL; 250 Î¼g/mL; 125 Î¼g/mL; 62.5 Î¼g/mL; 31.25 Î¼g/mL; 15.62 Î¼g/mL; 7.81 Î¼g/mL; 3.90 Î¼g/mL; 1.95 Î¼g/mL. Cytotoxicity test of IC50 using direct counting method and analyzed by probit analysis. Results: IC50 value of CZE in zam-zam and ethanol solvent were 28.24 Î¼g/ml and 13.71 Âµg/ml respectively at the same 24 hours incubation period. Chi-square test revealed p value was 0.000 (Î± = 0.05), meaning that there was significant relationship. Conclusion: CZE activity using ethanol is highly active while CZE using zam-zam water is moderate and both of them have the toxicity on breast cancer cell. As the result, apoptosis process may occur.